Development and application of targeted UHPLC-MS/MS methods for the analysis of 31 groups of cardenolide glycosides - Fock, Ville; Agrawal, Anurag; Salminen, Juha-Pekka (Elsevier, 2026)
Cardenolides are steroidal glycosides characterized by structural complexity and both medicinal and ecological relevance, necessitating precise and reliable analytical methods for their detection and quantitation. Although cardenolide MS/MS fragmentation has been extensively studied, no method has previously enabled simultaneous detection and quantitation of all glycosides derived from a given genin. In this study, we developed group-specific MS/MS methods for comprehensive screening of cardenolide glycosides containing 31 distinct genin backbones, i.e. aglycones. Application of these 31 genin-specific methods enabled detection of more than 300 glycosides in 23 plant species, several of which were represented in multiple tissue types. The approach successfully distinguished all genins from each other, including those with identical m/z values at the same time minimizing false positives from structurally related steroids such as bufadienolides and saponins. Method validations demonstrated low limits of detection (LOD) and limits of quantitation (LOQ), where the lowest limit of detection (LLOD) values varied between 1.5 and 74.6 ng/mL, apart from a single outlier exhibiting a substantially higher LLOD. Wide linear ranges were also achieved, with most upper limits of quantitation (ULOQ) between 1 and 5 μg/mL. Matrix effect and repeatability assessments indicated only minor variation for most methods. The genin-specific MS/MS strategy enables rapid, high-throughput analysis of cardenolide glycosides without loss of sensitivity or selectivity, where comparisons with compound-specific methods revealed only minor differences in analytical performance. These results highlight the robustness and effectiveness of the group-specific methodology for both qualitative and quantitative applications in cardenolide research.